The impact of individual factors on health information-seeking behavior of infertile couples undergoing assisted reproductive technologies: Longo model - Nader Alishan Karami; Masoomeh Latifi; Nilofar Berahmand; Fatemeh Eini; Mohammed N Al-Suqri (Advanced Biomedical Research, 2023)
Background: This study investigated the impact of individual factors on the Health information-seeking behavior (HISB) of infertile couples undergoing Assisted Reproductive Technologies (ART). Materials and Methods: This applied study was done using the descriptive-analytical method. The population of the study remains to be infertile couples undergoing ART referred to a public Infertility Center and a private one in Bandar Abbas (capital of Hormozgan province, Southern Iran) in the summer of 2020. Using simple random sampling, 168 people were selected. The data collection tool was a questionnaire extracted from Longo HISB Model, used after validation and reliability. Data were analyzed by SPSS software using descriptive and inferential tests. Results: The results showed that individual factors (gender, education, income, age, and cause of infertility) affect the HISB of infertile couples. Based on the analysis of variance, there was a significant difference between infertile couples concerning Passive Information Receipt (F = 2.688 and P = 0.048) so the couples with a male cause used Passive Information Receipt more. Conclusions: Considering the results, it is necessary for the country's health system to take appropriate measures to provide an appropriate situation for better decision-making for infertile couples and improve the chances of fertility by reducing the existing inequalities to Active Information Receipt and quality health information.